TECHNOLOGY OF ENERGY RECOVERY OF BIODEGRADABLE WASTE IN BIOGAS PLANT - KRUZLIAK, Ondrej; CERNECKY, Jozef (Trends in education, 2010)
The present contribution deals with problematic of using biodegradable waste by environmentally sound manner for environment. In this case, there are processed and used excrements of livestock for heat and electricity production process in cogeneration unit. The present describes the biogas production process, the technological equipment of plant and their mutual continuity in the process of biogas production too. There are reminded general advantages and disadvantages of waste processing by this technology. Students involve of the problematic of the waste treatment by alternative methods in field of study called ˝Ecotechnics˝.
Keywords: fermentation; biogas; biogas station; cogeneration unit.